1979
DOI: 10.1017/s0021859600060469
|View full text |Cite
|
Sign up to set email alerts
|

Rothamsted irrigation 1964–76

Abstract: A series of irrigation experiments was done at Rothamsted where the soil is a flinty silty clay loam over flinty clay. The results are compared with those obtained by Penman (1962, 1970, 1971) at Woburn where the soil is a loamy sand over sand. The limiting deficits, JD ( , above which irrigation increased yields, were about 2-6 times greater at Rothamsted than at Woburn; this ratio approximates to the ratio of the water-holding capacities of the soils (-0-1 to -15 bar) to a depth of 1 m. The limiting deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 16 publications
4
52
1
Order By: Relevance
“…Total rainfall (1 July 2011 to 30 June 2012) experienced by the lucerne crops was 580 mm at the stone free site and 645 mm at both stony sites which was accumulated in 52 rain days (>1 mm). Total Penman potential evaporation (P ET ) (French and Legg 1979) was 910 mm, and exceeded rainfall from about September to May. Long term mean annual rainfall for Lincoln is 630 mm and annual mean P ET is 1095 mm.…”
Section: Meteorological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total rainfall (1 July 2011 to 30 June 2012) experienced by the lucerne crops was 580 mm at the stone free site and 645 mm at both stony sites which was accumulated in 52 rain days (>1 mm). Total Penman potential evaporation (P ET ) (French and Legg 1979) was 910 mm, and exceeded rainfall from about September to May. Long term mean annual rainfall for Lincoln is 630 mm and annual mean P ET is 1095 mm.…”
Section: Meteorological Conditionsmentioning
confidence: 99%
“…The soil diffusion constant was 4.4 mm day -1/2 . Potential E s is set by P ET , and reduced proportional to ground cover (French and Legg 1979) which was calculated daily from interpolated LAI measurements. It was assumed E s only occurred in the top 0.2 m of soil, and to avoid overestimation, the Ritchie calculation was modified to account for additional soil drying by crop roots ).…”
Section: Soil Water Balance Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil water content in root zone was measured by using the gravimetric procedure of direct soil water measurement. The moisture content in root zone was computed by using the method as described by (Penman, 1970;French and Legg, 1979). Soil sampling from experimental plots (0-60 cm depth) was done on regular basis on alternate days with the help of soil sampling probe throughout cropping period (May-December) for determination of soil moisture.…”
Section: Experimental Sites and Treatments Detailmentioning
confidence: 99%
“…This is time consuming and expensive to measure directly. However, we have found that, the model of Penman [5], as refined by French and Legg [6], works well for annual arable crops. This model quantifies the yield response to drought by using the maximum potential soil moisture deficit (MPSMD) experienced during the growth of the crop as the measure of stress.…”
Section: Arable Cropsmentioning
confidence: 99%